2024
DOI: 10.1146/annurev-publhealth-040617-014746
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Evidence-Based Public Health: Reconciling the Pulls of Practice and the Push of Research

Abstract: Timely implementation of principles of evidence-based public health (EBPH) is critical for bridging the gap between discovery of new knowledge and application. Public health organizations need sufficient capacity (the availability of resources, structures, and workforce to plan deliver and evaluate the “preventive dose” of an evidence-based intervention) to move science to practice. We review principles of EBPH, the importance of capacity building to advance evidence-based approaches, promising approaches for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
281
0
25

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(332 citation statements)
references
References 169 publications
(214 reference statements)
3
281
0
25
Order By: Relevance
“…Provision of training and technical assistance with external partners is also essential to advance the work of state health department chronic disease units, since local partners both within and outside of the public health sector implement complex multi-level evidence-based approaches [2, 9, 11, 37]. One of the ten essential public health services is to mobilize community partnerships to address public health issues [6, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Provision of training and technical assistance with external partners is also essential to advance the work of state health department chronic disease units, since local partners both within and outside of the public health sector implement complex multi-level evidence-based approaches [2, 9, 11, 37]. One of the ten essential public health services is to mobilize community partnerships to address public health issues [6, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Health department staff and public health leaders emphasize the importance of clear communication of EBDM principles, expectations, and processes, and sharing of information across programs (2,911,1417). A health department in Ottawa, Canada, found that focusing solely on obtaining and disseminating evidence was not enough, as staff had to learn to think about different ways of approaching their jobs, which raised anxieties (10).…”
Section: Discussionmentioning
confidence: 99%
“…Health departments are directing resources to areas with poor health outcomes but lack of political will for EBDM persists in some corners. Skepticism about the effectiveness of prevention, racism and social inequality, and reluctance in some communities to partner across racial, economic, and rural/urban strata are common challenges requiring nontraditional transdisciplinary work (2). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These skills are critical to effective practice and to meeting Public Health Competencies, Public Health Accreditation Board Standards for EBPH, and workforce development goals (8–10). To recognize and deliver EBPH, public health agencies need sufficient capacity (ie, the availability of resources and structures, and a prepared workforce) (5,11). …”
Section: Introductionmentioning
confidence: 99%